Post-Thoracotomy Subcutaneous Emphysema Caused by Airway Blood Clot–Induced Barotrauma: A Rare Case Report - Kevin Christian Kamalo; Eka Yudha Lantang; Anastasia Magdalena Lantang; Yolanda Edith Pratiwi; Rigel Kent Paat (Jurnal Sehat Indonesia (JUSINDO), 2026)
Subcutaneous emphysema resulting from barotrauma caused by an airway blood clot is an extremely rare complication following thoracotomy, with few reported cases in the literature.  This case report aims to describe the clinical presentation, diagnostic findings, and management of a post-thoracotomy patient who developed subcutaneous emphysema secondary to barotrauma induced by blood clot airway obstruction.  A 27-year-old male patient with blunt thoracic trauma underwent exploratory thoracotomy and was postoperatively managed with mechanical ventilation. Data were collected retrospectively from medical records, following the 2013 CARE Guidelines. On the second postoperative day, the patient developed severe shortness of breath, tachypnea, and subcutaneous emphysema in the chest and neck. Chest X-ray confirmed subcutaneous emphysema, and bronchoscopy revealed black blood clots obstructing both main bronchi. Mediastinostomy and bronchoscopic clot removal were performed. Following bronchoscopy, the patient's respiratory condition improved significantly; he was extubated one day later and transferred from the ICU after eight days. Airway obstruction by a blood clot can trigger barotrauma and subcutaneous emphysema in post-thoracotomy patients on mechanical ventilation. Early bronchoscopy is recommended to prevent and manage such life-threatening complications.